API-579 Fitness for Service Assessment of Pig Launcher Pipeline on Bulge Defect Condition: A Case Study - Ramadhan, Fakih Ilham; Arief, Tria Mariz; Handoko, Yunendar Aryo; Saputro, Andy; Maulana, Mochamad Irvan (ROTASI, 2024)
Fitness for service (FFS) is the standard assessment procedure to evaluate an operation's worthiness of static equipment due to its defect condition. FFS ensures a safety aspect of operation and produces a strategic action due to a defect occurring on an object. During a regular inspection activities at oil and gas plant, four bulges were found on a pig launcher pipeline. The FFS assessment following the API-579 standard was conducted as a case study. The initial assessment result shows that the bulge defect's geometrical aspect did not comply the required criteria. Then, a stress analysis assessment was conducted which showed that the safety factor and the elastic stress criteria were successfully fulfilled. This concludes that the stress occurred in the pipeline is still in its elastic deformation region. However, the failure of remaining strength factor acceptance criteria to be fulfilled shows that there was a degradation of pipeline capability to be loaded with the operating pressure. This whole assessment concludes that rerate remediation should be taken before the pipeline is reoperated by decreasing the maximum allowable operating pressure from 9,27 MPa to 8,22 MPa.